I korndemonens bilde - Resløkken, Åmund Norum; Ødemark, John (Tidsskrift for kulturforskning, 2016)
Abstract This article examines the exhibition of folketro [popular belief] at Norsk folkemuseum [The Norwegian Museum of Cultural History]. The exhibition was inaugurated in 1938. The display of the cultural and religious category folketro was heavily influenced by the Norwegian ethnologist Nils Lid, who in turn had applied the theories and methods of W. Mannhardt and J. G. Frazer to Norwegian ethnological material. From its inception, the museum had a clear program; to mediate between the cultures of the country and the city, and thus create a unifying "mirror image" of the cultural history of the Norwegian people that would serve a reconciliatory function in the "cultural wars" between proponents of rural and elite/city culture. In the article, we are concerned with how the exhibition of folk belief was inscribed in a museum framework established in the beginning of the century. Firstly, we argue that the museum’s organization of cultural time foreshadows the histori-cal multi-temporality associated with the history of the mentalities. Secondly, we demon-strate that the exhibition of folketro introduced an anthropological dimension in the museum that went way beyond the national, and back to a time of origin where sacrificial customs connected to the figure of the Corn demon had constituted folk belief as a trans-cultural category.